The Atherosclerotic Plaque Vulnerability: Focus on the Oxidative and Endoplasmic Reticulum Stress in Orchestrating the Macrophage Apoptosis in the Formation of the Necrotic Core - Cominacini, Luciano; Garbin, Ulisse; Mozzini, Chiara; Stranieri, Chiara; Pasini, Andrea; Solani, Erika; Alessandra Tinelli, Irene; Fratta Pasini, Anna (Current Medicinal Chemistry, 2015)
Although the understanding the pathophysiology of atherogenesis and atherosclerosis progression has been one of the major goals of cardiovascular research during the last decades, the precise mechanisms underlying plaque destabilization are still unknown. The disruption of the plaque and the thrombosis in the lumen that are mostly determined by the expansion of the necrotic core (NC) are driven by various mechanisms, including accelerated macrophage apoptosis and defective phagocytic clearance (defective efferocytosis). Oxidative stress is implicated in the expansion of the NC: in fact, many oxidized compounds and processes contribute to the macrophage apoptosis; in addition, the oxidized derivatives of polyunsatured fatty acids promote defective efferocytosis, with the final result of NC expansion. In the last years the role of the endoplasmic reticulum (ER) stress is under investigation to better define its possible contribution in affecting the NC expansion. The abnormal amount of apoptotic cells in the vulnerable plaque has been demonstrated to be related both to the sustained ER stress and to the expression of survival and protective genes, such as the unfolded protein response or/and the nuclear erytroid- related factor 2. In this review the authors focus on the promising results of the oxidative and ER stress in contributing to triggering and orchestrating the atherosclerotic plaque vulnerability.
Keywords: atherosclerosis